Pengaruh Layanan Informasi Dengan Model PBL Terhadap Perencanaan Studi Lanjut Siswa UPT SMP Negeri 8 Medan - Novrida Ginting; M. Fikri Ryan Dhani; Lilis Granella Sidabutar; Kevin Romie; Khairunnisa Sipahutar; Nadra Hasina Tanjung; Adelia Mauritia Shalsa (CV. ITTC INDONESIA, 2025)
This study aims to determine the effect of information services using the project-based learning model on further study planning for class IX-7 students at UPT SMP NEGERI 8 Medan. This research uses a quasi-experimental quantitative approach. The research subjects were 31 students of class IX-7. The data were collected using a validated and reliable questionnaire, given before and after the information service. The average pre-test score was 74, and the average post-test score was 133, with an increase of 59 points or 44%. The paired sample T-test results showed Sig. (2-tailed) of 0.000 < 0.05 and t-count of 21.176 > t-table of 1.697. This means that information services using the project-based learning model positively and significantly influence further study planning for students.